Sorghum biscuits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
These biscuits are made from 50% of white sorghum or maize and are manufactured exactly like traditional biscuits made from 100% wheat flour. Using locally grown cereals is an economic advantage, and they have proved popular with consurners, who...